EVALUATION OF KNOWLEDGE AND PRACTICES OF FOOT CARE IN PATIENTS WITH CHRONIC TYPE 2 DIABETES MELLITUS - Gondal, Murtaza; Bano, Uzma; Moin, Shaheen; Afridi, Zia ud Din; Masood, Rehan; Ahmad, Anis (Journal of Postgraduate Medical Institute, 2011)
Objective: To evaluate the knowledge and practices of foot care in patients with diabetes mellitus and to stress upon the importance of such knowledge and practices in decreasing morbidity associated with diabetic foot disease. Material and Methods: One hundred patients of either sex from three tertiary care hospitals with a 5 year history of Diabetes Mellitus were selected in this study and were asked to fill out a questionnaire about their knowledge and practices about daily foot inspection, foot cleaning, appropriate nail care, and use of footwear in the form of shoe material, open or closed forepart and nature of heel. Results: Out of 100 patients (36 males and 64 females), 34% patients inspected their feet daily and 78% of the respondents knew about care of callosities, minor injuries and cuts, 52% of patients didn't know about correct technique of cutting nails. Eight (22.2%) male and 28 (43.8%) female patients were using open shoes while 24 (66.7%) male and 38 (59.4%) female patients had shoes with narrow forepart. Ten (27.8%) males were using shoes made of hard material as compared to 20 (31.3%) of female patients. Twenty two (34.4%) of our female diabetic patients were using shoes with high heel. Only 68% of the patients were on regular follow up. Conclusion: This simple quality initiative concludes the notion that patients with diabetes who are at risk for the development of diabetic foot ulcers should receive ongoing foot-specific patient education.